2003
DOI: 10.1042/bj20030177
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the pH-dependent pre-steady-state and steady-state kinetic characteristics of cysteine-proteinase mechanism: evidence for electrostatic modulation of catalytic-site function by the neighbouring carboxylate anion

Abstract: The acylation and deacylation stages of the hydrolysis of N -acetyl-Phe-Gly methyl thionoester catalysed by papain and actinidin were investigated by stopped-flow spectral analysis. Differences in the forms of pH-dependence of the steady-state and pre-steady-state kinetic parameters support the hypothesis that, whereas for papain, in accord with the traditional view, the rate-determining step is the base-catalysed reaction of the acyl-enzyme intermediate with water, for actinidin it is a post-acylation conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Previous studies in papain indicated that the reactivity of the catalytic cysteine is due to formation of an ion-pair with the catalytic histidine, analogous to the activation of the catalytic serine in the eponymous serine proteases by histidine. 26 UCHL1 has been thought to be papain-like in mechanism of action, but our observation suggests that this may not necessarily be the case. The cysteine may be reactive enough without participation by the histidine, perhaps due to a lowered pK a .…”
mentioning
confidence: 61%
“…Previous studies in papain indicated that the reactivity of the catalytic cysteine is due to formation of an ion-pair with the catalytic histidine, analogous to the activation of the catalytic serine in the eponymous serine proteases by histidine. 26 UCHL1 has been thought to be papain-like in mechanism of action, but our observation suggests that this may not necessarily be the case. The cysteine may be reactive enough without participation by the histidine, perhaps due to a lowered pK a .…”
mentioning
confidence: 61%
“…The evaluation of ester hydrolysis as a function of substrate concentration allowed for the estimation of the rate constants of the kinetic mechanism and is consistent with a double displacement (ping pong) mechanism. Unlike related enzymes (23,38,39), the burst rate of 3CL promediated ester hydrolysis was shown to be independent of substrate concentration. The 3CL pro burst rate observations can be accounted for if there was a high commitment to catalysis: the acylation rate (k 2 ) is much faster than the substrate dissociation rate (k -1 ).…”
Section: Discussionmentioning
confidence: 84%
“…Unlike the ester substrates, the amide substrates have a hydrogen bond donor in the scissile bond, which has been shown to have a significant role in catalysis for other proteases (23,(30)(31)(32)(33). Because of insufficient solubility and higher K m values, peptides 4 and 5 could not be saturated under pre-steady-state experimental conditions.…”
Section: Resultsmentioning
confidence: 96%
“…Actinidin has a wide substrate specificity, hydrolyzes most strongly the amide and ester bonds at the carboxyl side of a lysine residue and it is active at pH range 4-10 (Arcus, 1959;McDowall, 1970;Hussain et al, 2003;Morimoto et al, 2006). It is composed of 220 amino acid residues with molecular mass of 23.5 kDa (Carne and Moore, 1978;Baker, 1980;Watts and Brocklehurst, 2004).…”
Section: Introductionmentioning
confidence: 95%